Organizational Communication in Improving the Work Motivation at Diskominfo Makassar - Salsabila; Hidayahni Amin, Fatimah; Luhriyani Sunusi, Seni (Celebes Journal of Language Studies, 2025)
This research aims to find out the ways the employees use their organizational communication and the employees’ difficulties in using organizational communication in improving the work motivation. This research uses a qualitative research design with a descriptive approach to describe the research subject. Data collection techniques used observation and audio recording and interview questions. The result of this study shows that the use of organizational communication can improve employees' work motivation. In this study, the employees used communication with five functions, namely informative, regulative, persuasive, integrative, and subordinate manager. They also use certain language functions in improving work motivation which is divided into internal and external factors. This study also found difficulties in communication, namely technical barriers, semantic and psychological barriers, physical barriers, framework of thought barriers, and cultural barriers. Communication in organizations can establish good relationships between employees and can improve employee motivation.